The Role of Islamic Financial Inclusion in Promoting Economic Growth: Empirical Evidence from Sumatera, Indonesia - Marabona Munthe; Putri Jamilah; Fitri Fitri; Edi Haryono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to examine the relationship between Islamic financial inclusion and its dimensions on economic growth. To obtain multilateral results, we have prepared panel data for 10 provinces on the island of Sumatra and conducted not only static panel estimation (fixed effects, robust standard errors) but also dynamic panel estimation using the generalized system method of moments (GMM) approach that controls for endogeneity. Based on the estimation results, we found that Islamic financial inclusion significantly influences economic growth. Furthermore, the three dimensions of Islamic financial inclusion (Accessibility, Availability, and Usefulness) are important factors in economic growth. Therefore, to support financial inclusion in the future, investment policies in infrastructure and improvement of Islamic financial services are needed. The results of this study emphasize the importance of policies that support the growth and development of Islamic financial services, which have been shown to play a significant role in increasing economic growth through the development of an inclusive financial system. Based on the author's literature review and research gap analysis, no studies have used the Islamic financial inclusion index and tested it against economic growth. Similarly, the author found no studies that specifically explored the dimensions of Islamic financial inclusion (IFII). This study fills this research gap.